ACUTE ULNAR NERVE PALSY SECONDARY TO GANGLION CYST AT GUYON'S CANAL: A CASE REPORT (Asian Journal of Medical Research and Health Sciences, 2026)
Ulnar nerve compression at the wrist is an uncommon neuropathy, often caused by space occupying lesions within Guyon's canal. Ganglion cyst is a recognized but relatively rare aetiology, particularly in elderly patients presenting with acute symptoms. A 70-year-old woman presented with acute onset ulnar nerve palsy of 10 days’ duration, two months after undergoing aortic valve replacement. She was on anticoagulant therapy with T.Rivaroxaban 10mg twice daily. Clinical examination revealed motor weakness in the ulnar nerve distribution with relative sensory sparing. Musculoskeletal Ultrasound examination demonstrated a cystic lesion consistent with a ganglion within Guyon's canal, compressing the ulnar nerve. Nerve conduction studies supported localization to the wrist. Surgical excision resulted in complete recovery within two weeks. Structural causes such as ganglion cysts should be considered in acute ulnar neuropathy. Early diagnosis and surgical management can yield excellent outcome particularly in patients presenting with neurological deficit.